Culturing Participatory Culture to Promote Gen-Z EFL Learners’ Reading Proficiency: A New Horizon of TBRT with Web 2.0 Tools in Tertiary Level Education - Parvin Murshida; Muftah Muneera (Open Education Studies)
Task-based language teaching (TBLT) is widely recognized as an effective approach for developing second language (L2) learners’ English skills. However, its success often depends on the teacher’s ability to design engaging tasks and dynamic learning platforms that foster active participation. While previous studies highlight the importance of integrating technology with TBLT to enhance L2 learning, there is limited research on optimizing reading tasks for Generation-Z learners. This study seeks to bridge this gap by exploring how Web 2.0 social tools can be integrated into interactive learning platforms to improve reading comprehension. The study examines the effectiveness of collaborative reading tasks in promoting automatic word recognition, background knowledge activation, and inference-making – key components of reading proficiency. Using an experimental design, the study observes 35 EFL undergraduate students enrolled in the 2023 academic year. Data collection includes a collaborative learning skill checklist and a survey questionnaire with open-ended questions. Findings indicate that blogs and discussion boards significantly enhance interaction and collaboration, leading to improved language processing and knowledge production. These results emphasize the potential of Web 2.0 tools in TBLT to foster equitable reading skills. The study concludes with practical recommendations for educators integrating technology into reading instruction.